Assessing cognitive functioning in older adults and its relationship to quality of life : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate of Clinical Psychology at Massey University, Wellington, New Zealand - Callow, Lauren May (Massey University, 2013)
Cognitive impairment of any magnitude carries an undetermined societal and individual cost. The desire to accurately predict cognitive decline at an early stage is sought-after as robust cognitive health and function in later life is desirable. Knowing who is at risk and what those risks may be is imperative for targeting interventions to those in need. The lack of nationally representative information regarding cognitive functioning means that there is little information about base rates of cognitive functioning. This represents a problem in terms of gauging the incidence of cognitive impairment and difficulties related to planning for social and health expenditure for the ageing population. This thesis explores the validity and reliability of the Addenbrooke’s Cognitive Examination-Revised and develops New Zealand norms for the measure using data from the New Zealand Longitudinal Study of Ageing. These demographically stratified norms will help to determine those people who may be more vulnerable to a dementing process. The information is applied in the context of examining the impact of cognitive functioning on quality of life; an important concept to consider in research. In article one, a pilot study of the use of the Addenbrooke’s Cognitive Examination-Revised (ACE-R) with older community dwelling adults, the utility of the measure was supported. In article two, the ACE-R was integrated into a nationwide longitudinal study of older adults. Stratified demographic norms were created. This is the first known nationally representative New Zealand study to provide evidence of the impact of age, gender and ethnicity on measures of cognitive functioning. In article three this information was applied in the study of the relationship between cognitive functioning and quality of life. Results suggested that cognitive functioning has a small significant association with quality of life in older age and a much larger association in those who display cognitive functioning difficulties. This research adds to the research base in New Zealand by providing representative norms from which older adults can be compared in a meaningful and specific way.
Irregular page numbering. page ix and 9.
Keywords: Cognitive functioning; Cognition in old age; Older people's quality of life